Effects of Electronic Media Advertising on Rural Banking in Ghana: A Study of Unity Rural Bank Limited, Ho Ghana - Nyarko, Israel Kofi (Journal of Asian Business Strategy, 2013)
Advertising which uses electronic energy to transmit information to the end user is called electronic media advertising. It appears as TV, radio, internet. The objective of this study is to establish the contribution of electronic media advertising to rural banking in Ghana. Hitherto, studies have covered advertising rural banks; the outcome of this study will help reveal contributions of electronic media ads to rural banking. Questionnaires were administered to 350 rural bank customers in Ho Municipality. Statistical Package for Social Sciences (SPSS) was used to analyze the data. It was found that radio advertising is the main tool adopted by Unity Rural Bank and this has influenced many customers to the bank. Thus, it‟s important that the bank air radio ads often to improve patronage. The study shows that traders constitute an important market of rural banks; traders should be major target and create ads to attract them.